Validation of Standard of Living Scale with Comparison to Other Socio-Economic Scales in a Semi Urban Area of Mangalore : A Pilot Study - Priyadarisini, N. J.; K., Rashmi; Kiran, N. Udaya; Badiger, Sanjeev (Journal of Health and Allied Sciences NU, 2016)
Introduction: Socioeconomic status is an important determinant of health condition of an individual or a family. Many tools are being used to assess the socioeconomic status. Each of the scales have their own advantages and disadvantages. But an appropriate and a standardized tool is yet to be developedObjectives: To compare the standard of living based on different socioeconomic scales in a semiurban area of Mangalore and to assess the appropriateness of socioeconomic scales to be used in a semiurban area of MangaloreMethodology: A cross sectional study was conducted in households of Kuthar and Manjanady villages of Dakshina Kannada district from June- August 2014. Questionnaire method was used to avail information about the socioeconomic status of the study population. The data was analysed using SPSS 16 software.Results: Majority (70%) of the study population belonged to class IV of kuppuswamy scale. Whereas according to Modified BG Prasad scale majority of the population belonged to class III (35%) and class II (28%). According to Pareek's scale around 92% of population belonged to class IV. But when standard of living was assessed majority of them (62%) had high standard of Living.Conclusions: We found that Standard of living is the better option in assessing the socio-economic status of a household as compared to all other scales whether be it urban, rural or semi urban.
Keywords: socio economic status; different socioeconomic scales; Modified Kupuswamy scale; Pareek scale; Modified BG prasad scale and standard of living index